ASASSN-18aan: An eclipsing SU UMa-type cataclysmic variable with a 3.6-hr orbital period and a late G-type secondary star. (7th February 2021) - Wakamatsu, Yasuyuki; Thorstensen, John R; Kojiguchi, Naoto; Isogai, Keisuke; Kimura, Mariko; Ohnishi, Ryuhei; Kato, Taichi; Itoh, Hiroshi; Sugiura, Yuki; Sumiya, Sho; Matsumoto, Hanami; Ito, Daiki; et al.
Abstract: We report photometric and spectroscopic observations of the eclipsing SU UMa-type dwarf nova ASASSN-18aan. We observed the 2018 superoutburst with 2.3 mag brightening and found the orbital period ( P orb ) to be 0.149454(3) d, or 3.59 hr. This is longward of the period gap, establishing ASASSN-18aan as one of a small number of long- P orb SU UMa-type dwarf novae. The estimated mass ratio, [ q = M 2 / M 1 = 0.278(1)], is almost identical to the upper limit of tidal instability by the 3 : 1 resonance. From eclipses, we found that the accretion disk at the onset of the superoutburst may reach the 3 : 1 resonance radius, suggesting that the superoutburst of ASASSN-18aan results from the tidal instability. Considering the case of long- P orb WZ Sge-type dwarf novae, we suggest that the tidal dissipation at the tidal truncation radius is enough to induce SU UMa-like behavior in relatively high- q systems such as SU UMa-type dwarf novae, but that this is no longer effective in low- q systems such as WZ Sge-type dwarf novae. The unusual nature of the system extends to the secondary star, for which we find a spectral type of G9, much earlier than typical for the orbital period, and a secondary mass M 2 of around 0.18 M ⊙, smaller than expected for the orbital period and the secondary's spectral type. We also see indications of enhanced sodium abundance in the secondary's spectrum. Anomalously hot secondaries are seen in a modest number of other CVs and related objects. These systems evidently underwent significant nuclear evolution before the onset of mass transfer. In the case of ASASSN-18aan, this apparently resulted in a mass ratio lower than typically found at the system's P orb, which may account for the occurrence of a superoutburst at this relatively long period.